Solar-Powered IoT Gas Monitoring System with Vibration Alerts for Deaf Users - Abdul Munir, Abdul Mutalib; A. Jalil@Zainuddin, Mohd. Hafiz (Evolution in Electrical and Electronic Engineering, 2026)
This research focuses on developing a Solar-Powered IoT Gas Monitoring System with Vibration Alerts for Deaf Users to enhance safety in residential and commercial environments. The system utilises solar energy with battery backup to ensure continuous operation during power outages, while the alternating current (AC) supply serves as the primary power source. An automatic power transfer mechanism is implemented to maintain uninterrupted operation of critical components, particularly the gas detection and IoT monitoring modules. The Internet of Things (IoT) technology helps continuously monitor gas levels and sends early notifications to users. In cases of hazardous gas levels, various safety features are triggered, such as an alarm buzzer, an LED alarm, the starting of exhaust fans, and automatic control of a gas solenoid valve to restrict gas leakage. In addition, a vibration-based alert bracelet is incorporated for vibration alarms for deaf and hard-of-hearing individuals. This ensures effective non-auditory alerts for the deaf. Results from experiments confirm that the system can detect gas leakage and hazardous gas levels, as well as activate safety alarms and issue vibration alerts for deaf individuals, in real time. Overall, the developed system demonstrates strong potential as a reliable, inclusive, and sustainable safety solution for modern home and commercial applications.